High performance of an enzyme linked immunosorbent assay for American tegumentary leishmaniasis diagnosis with Leishmania (Viannia) braziliensis amastigotes membrane crude antigens - Bracamonte, María E. (PLoS One, 2020)
The diagnosis of American tegumentary leishmaniasis (ATL) still requires the design of more effective tools. Leishmania (Viannia) braziliensis is the causal agent of the 90% of Argentinean ATL cases. Considering the current knowledge, an ELISA based crude antigen (CA) for the diagnosis was designed. Ninety-nine subjects diagnosed as ATL, 27 as no-ATL, and 84 donors from non-ATL-endemic areas were included in this study. The current ATL diagnosis was based four techniques, dermal smear microscopic examination (parasitological test), PCR, Leishmanin skin test, and clinical records. We obtained CA extracts from promastigotes and amastigotes from macrophage cultures of different zymodemes of endemic Leishmania species circulating in the study area. Crude antigens from the ‘local’ main zymodeme of L. (V.) braziliensis showed the highest reactivity against anti-Leishmania antibodies compared to the other included species. The CA of amastigotes of this zymodeme was 3.4 fold more reactive than promastigotes one. Moreover, amastigote-membrane CA (MCA) were 3.6 fold more reactive than the soluble antigens. The MCA-ELISA reached a sensitivity and specificity of 98% (CI = 94.7%-100%) and 63.6% (53.9–73.1), respectively. When anti-Trypanosoma cruzi reactive sera were excluded, the specificity reached 98.4% (94.4–100), while the sensitivity was similar, with a positive predictive value (PV) of 98.6% (94.6–100) and negative PV of 96.3% (91.6–100). The performance of the MCA-ELISA results strongly contribute to the final diagnostic decision, since a non-reactive serological result almost discards the suspected ATL, because of its high negative PV. The developed MCA-ELISA showed a high diagnostic performance, which makes it a good candidate for ATL diagnosis, for seroprevalence studies, or for monitoring treatments efficacy.